2022
DOI: 10.1007/s11064-022-03751-5
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of the ROS Inhibitor Phenyl-N-tert-butylnitrone Alleviates Sleep Deprivation-Induced Hyperalgesia by Suppressing Microglia Activation and NLRP3 Inflammasome Activity in the Spinal Dorsal Cord

Abstract: Sleep deprivation, a common perioperative period health problem, causes ocular discomfort and affects postsurgical pain. However, the mechanism of sleep deprivation-induced increased pain sensitivity is elusive. This study aims to explore the role of ROS in sleep deprivation (SD)-induced hyperalgesia and the underlying mechanism. A 48-h continuous SD was performed prior to the hind paw incision pain modeling in mice. We measured ROS levels, microglial activation, DNA damage and protein levels of iNOS, NLRP3, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Using the PWMT as an indicator pain, we found that SD decreased the pain threshold in mice, while spontaneous pain had not yet transpired, as result that persisted for approximately 10 days. This finding slightly deviates from the research results of Huang et al, 22 and may be attributed to differences in the duration of SD induction and the age of mice. More importantly, SD significantly increased and prolonged postoperative incisional pain.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Using the PWMT as an indicator pain, we found that SD decreased the pain threshold in mice, while spontaneous pain had not yet transpired, as result that persisted for approximately 10 days. This finding slightly deviates from the research results of Huang et al, 22 and may be attributed to differences in the duration of SD induction and the age of mice. More importantly, SD significantly increased and prolonged postoperative incisional pain.…”
Section: Discussioncontrasting
confidence: 99%
“…The mouse SD model was induced in an SD chamber, as previously described. 22 In brief, mice subjected to SD were placed in an SD chamber (Xinruan, China) for 4.5 days and kept awake by a continuously rotating metal bar, which was set to the same speed, force, and direction of rotation to minimize experimental error. Food and water were placed on the walls of the chamber for the mice to take freely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep loss may cause the accumulation of proinflammatory cytokines in blood and this may be cause by Enhanced efflux through the BBB [ 40 ]. Our previous study found that SR-induced hyperalgesia is associated with the inflammation of the spinal dorsal cord [ 27 ]. Consistently, our findings of increased levels of pro-inflammatory factors in the spinal cord and activation of glia confirmed the previous conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…[9] ROS plays a role in glutamatedependent long-term potentiation (LTP) and that moderate levels of ROS are vital for neuronal growth and development. [10] Studies have demonstrated that SD is accompanied by decreased antioxidant and increased ROS, [11][12][13] meanwhile leading to elevated levels of plasma pro-inflammatory factors such as tumor necrosis factor (TNF)-𝛼 and interleukin (IL)-1𝛼. [14] Silent information regulator factor 2-related enzyme 1 (Sirt1), a nicotinamide adenine dinucleotide-dependent histone deacetylase, regulates cellular responses to injury like antioxidant defense and apoptosis.…”
Section: Introductionmentioning
confidence: 99%